Kvβ1.1 associates with Kvα1.4 in CHO cells and pigeon type II vestibular hair cells and enhances the amplitude, inactivation and negatively shifts the steady-state inactivation range - Correia, Manning J. (2008)
Although A-type potassium currents are found in type II hair cells in the inner ear of most species, the molecular mechanisms for activation and inactivation of the I(A) current remain unknown. In frog semicircular canal hair cells, for example, there appears to be two classes of currents having either fast or slow inactivation (Norris et al., 1992; Russo et al., 2007). It has been suggested that somehow the “ball and chain” mechanism (N-terminus motif) is modified by alternative splicing to account for the two classes of inactivation. To examine other possibilities, we cloned alpha and beta subunits that comprise the A-type potassium channel complex in adult and embryonic pigeon brain, cochlea and labyrinth. By sequence homology, we concluded that the subunits present were Kvα1.4 and Kvβ1.1. The sequence of the open reading frame for Kvα1.4 contained the N-terminus, pore and C-terminus motifs for N-and C-type inactivation. The sequence for Kvβ1.1 displayed amino acids consistent with assembly and association with Kvα1.4 alpha subunits. Kvα1.4 and Kvβ1.1 were transfected either singly or in combination into CHO cells. These cells and native hair cells from the pigeon utricle were patch clamped and the inactivation properties of the A-type current were studied. In the native hair cells, the A-type current was identified by its pharmacological (4-AP; IC(50) = 11μM) and voltage dependent inactivation properties. A comparison of the mean time constants from best fitted single exponential and sum of two exponential equations to the ionic current inactivation revealed the following. In CHO cells when Kvα1.4 was expressed alone, the mean time constant (τ(1) = 107 ms ±19, N =32) was significantly (P < 0.001) longer and the mean peak amplitude (2.28 nA ±0.39, N=32) was smaller than when Kvα1.4 and Kvβ1.1 were expressed in CHO cells. Moreover, the co-transfection of Kvα1.4 and Kvβ1.1 into CHO cells caused a shift in the steady state inactivation curve parameter Vo 30 mV in the hyperpolarized direction relative to CHO cells expressing only Kvα1.4. Similarly, Kvα1.4 transfected CHO cells produced longer time constants and smaller amplitudes than those found for native utricular hair cells. These data lead us to conclude that while the amino acid motifs are present in Kvα1.4 and Kvβ1.1 to suggest N-and C-type inactivation, co-assembly and association of Kvα1.4 and Kvβ1.1 may also produce changes in the time dependent inactivation properties of vestibular hair cells.